The Role of Self-Efficacy in Moderating the Effect of Motivation, Digital Literacy, and Educational Internships on Pedagogical Competence - Alrizqi, Damas Gianlugi; Kardoyo, Kardoyo; Oktarina, Nina (Universitas Negeri Semarang, 2024)
This research aims to determine the role of self-efficacy as a moderator between motivation, digital literacy, and educational internships on pedagogical competence. The type of research is quantitative. The population of this research is the students of UNNES Economics Education. The number of samples in this study is 157 respondents. The research result shows that motivation to become a teacher and digital literacy have a positive effect on pedagogical competence. Internship education does not affect pedagogical competence. Self-efficacy includes the effect of motivation to become a teacher on pedagogical competence. Self-efficacy strengthens the effect of digital literacy on pedagogical competence. Self-efficacy is unable to moderate the effect of internship education on pedagogical competence.